Anatomy of a route: Script analysis of irregular migration, smuggling and harms on the Central Mediterranean route to Europe - Bish, Alexandre (Criminology & criminal justice, 2025)
Since the so-called ‘migrant crisis’ in 2015, there has been intense policy interest around irregular migration along the Central Mediterranean Route to Europe. Despite increased research focus on this route, the details and geographical intricacies of these migration journeys have scarcely been examined. In this study, we investigate the what, where and how of the journeys of 71 people who travelled from Libya across the Mediterranean Sea to Malta. To do so, we break down their journeys into scripts (i.e. sequences of activities) and represent them as a composite script graph. We find that journeys were long – 18 months on average – and circuitous, involving diverse and complex geographical paths. Smuggling, brokerage and working during transit were key aspects of most journeys. Worryingly, two-thirds of participants experienced detention and/or forced labour before reaching Malta. By pinpointing where and how harm occurs, the composite script graph can support policy makers in reducing harm, including by accounting for the possible harm that interventions may cause, directly or as a result of displacement.